VD_FINDINFO Jug / 2022 / 441 vom 19. Januar 2022 - VD Tribunal cantonal (2022)
INJURE, MENACEDROIT PÉNAL, VIOLENCE CONTRE LES AUTORITÉS, DIRECTIVEINJONCTION | 106 CP, 177 al. 1 CP, 180 al. 1 CP, 180 al. 2 let. a CP, 285 ch. 1 CP, 66a al. 2 CP, 94 CP, 25 LContr